Challenges and opportunities for improving nitrogen utilization efficiency for more sustainable pork production - Shurson, Gerald C.; Kerr, Brian J. (Frontiers in Animal Science, 2023)
Pork is one of the most consumed animal-derived protein sources around the world, but less than 45% of dietary nitrogen (N) is converted into edible lean meat. This inefficiency contributes to the 80% of human-induced N emissions that have resulted in exceeding the planetary boundaries for N. Reducing this inefficiency requires using a multifaceted approach. Swine genetic selection programs have improved the rate of lean growth in recent decades, but further improvements may be difficult because of lack of genetic variation within the global pig population. Breeding programs to increase litter size have led to intrauterine growth restriction and an increased proportion of low-birth-weight piglets which do not utilize dietary protein as efficiently as normal birth weight pigs. Intact males have greater lean growth rate and N efficiency than castrates and gilts, and the use of immunocastration technology has been implemented in some countries to capture this benefit while minimizing boar taint in pig meat. Use of other metabolic modifiers including porcine somatotropin and ractopamine, alone or in combination with immunocastration, can further enhance lean growth and dietary N efficiency, but a general lack of consumer acceptance and potential food safety concerns have led to regulatory restrictions in many countries. Because feed production contributes about 70% of N emissions in pig production systems, use of precision feed formulation and feeding practices, selected dietary feed additives, feed processing, and minimizing feed wastage appear to offer the greatest opportunity to reduce N waste and environmental footprint to improve the sustainability of pork production.Both GCS and BJK contributed to the conceptualization, data curation, analysis, writing, reviewing, and editing of this manuscript.No research funding was provided.None.